VD_FINDINFO Décision / 2013 / 67 vom 6. Dezember 2012 - VD Tribunal cantonal (2012)
SUSPENSION DE LA PROCÉDURE, OUVERTURE DE LA PROCÉDURE | 309 al. 1 let. a CPP (CH), 314 CPP (CH), 393 al. 1 let. a CPP (CH)